Development of Textbooks to Support Mardeka Curriculum Learning on Basic Laws of Chemsitry Materials around Us - Lazaro Sofian Arif; Mawardi Mawardi; Okta Suryani (Universitas Pendidikan Mandalika, 2023)
Abstract The objective of this research is to create educational materials for the Mardeka curriculum that focus on fundamental chemical principles. The study adopts the Educational Design Research (EDR) approach, utilizing the plomp development model consisting of three stages: initial investigation, development, and prototype formation. To gather data, validity questionnaires and practicality questionnaires were employed. The developed textbooks underwent validation by five individuals, including three chemistry lecturers from FMIPA UNP and two chemistry teachers from SMAN 8 Padang. Additionally, practicality testing involved nine high school students from Phase E and two chemistry teachers from SMAN 8 Padang. The data analysis employed a Likert scale, employing Aiken's V formula to assess textbook validity and the modified Purwanto formula to assess practicality. The analysis of the data revealed that the product validation by the five validators yielded an average score of 0.86 indicating the textbooks' validity. Furthermore, the practicality evaluation by students and chemistry teachers yielded an average score of 92% and 95% respectively, indicating a high level of practicality. In conclusion, based on the data analysis, it can be inferred that the developed textbooks on the basic chemical laws are both valid and practical for use in chemistry education.